Benin : Third Review Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Benin. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
The growth momentum continues, driven by strong port activity, high cotton production, and the recovery of the Nigerian economy. The 2019 budget will bring the commitment-based fiscal deficit below the WAEMU convergence criterion of 3 percent of GDP next year. Program implementation remains satisfactory with all end-June 2018 quantitative performance criteria (QPCs) met; but the continuous QPC on non-accumulation of new domestic arrears was breached over March-June due to an institutional oversight.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Benin